Structural and magnetic properties of co doped zno films - Çakıroğlu, Münevver (My University, 2008)
Co KATKILI ZnO FİLMLERİN YAPISAL VE MANYETİK ÖZELLİKLERİNİN İNCELENMESİ Co katkılı ZnO filmlerin ve toz numunesinin yapısal ve manyetik özellikleri çalışılmıştır. Zn (1-x)Co(x)O filmler ve toz numuneler, sol-gel yöntemi ile hazırlanmıştır. Zn (1-x)Co(x)O ince filmleri, cam altlık üzerine sol-gel daldırma yöntemi kullanılarak üretilmiştir. Yapısal karakterizasyon; x-ray, Atomik Kuvvet Mikroskobu (AFM), Taramalı Elektron Mikroskobu (SEM) ve Enerji Dağılım Spektrometresi (EDS) ölçümleri ile belirlenmiştir. Manyetik ölçümler, Kuantum Design PPMS ile ölçüldü ve manyetik alan filme paralel olarak uygulandı. Manyetik ölçüm sonuçlarına göre 0.25 Co konsantrasyonuna sahip Zn (1-x)Co(x)O filmleri 305K sıcaklıkta ferromanyetik özellik gösterdiler.

STRUCTURAL AND MAGNETIC PROPERTIES OF Co DOPED ZnO FİLMS Structural and magnetic properties of cobalt doped ZnO films and powders were studied. Zn (1-x)Co(x)O films and powders were prepared by sol-gel method using solutions of Zn, and Co, based organometallic compounds. Zn (1-x)Co(x)O thin films were produced on glass substrate by a sol-gel dip coating technique. The surface morphologies and thermal properties of samples were investigated by AFM, SEM, EDS and DTA. The crystal and phase structures of the Zn (1-x)Co(x)O film and powder were characterized using x-ray diffraction (XRD). Magnetic measurements were performed with a Quantum Design PPMS with a magnetic field applied parallel to the film. The analysis of the magnetization measurements indicates that Zn (1-x)Co(x)O films with the Co concentration of 0.25 exhibit ferromagnetism at 305 K. Micrographs of the film revealed pinhole-free, crack-free, smooth and dense microstructures.
Keywords: Filmler_Işınlar; Metal